Disclosure about corporate social responsibility through ISO 26000 implementation made by Saudi listed companies - Lassaad Ben Mahjoub (Cogent Business & Management, 2019)
The paper examines the corporate social responsibility (CSR) reporting conducted by Saudi listed firms based on the guidelines of ISO 26000. To measure the extent of ISO disclosure, we use a content analysis. A CSR reporting index is established throughout the global reporting initiative (GRI) and the ISO 26000's seven core subjects of social responsibility. These sources inform the measurement of the level of CSR information reported in different documents (e.g., annual reports, sustainable development reports, etc.) published by these companies during the period 2015-2017. First, we conducted this study to explore the reactions of Saudi firms to the implementation of the new ISO 26000, and we searched for the most significant determinants of this reporting in Saudi listed companies. Second, we tested the bidirectional link between CSR reporting through Saudi market information asymmetry. The results showed that all the sampled firms included some ISO 26000 reporting in their published documents. Nevertheless, most reporting levels were weak. However, the results showed also a positive effect of CSR reporting based on ISO 26000 on information asymmetry.
Keywords: 650; Corporate Social Disclosure; ISO 26000; Saudi Listed Companies; Sustainability; content analysis; Information asymmetry